Zavedení shody se standardem TISAX do společnosti - Tesařová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce se věnuje implementaci shody se standardem TISAX ve společnosti působící v automobilovém průmyslu. Její první část uvádí teoretický podklad pro danou problematiku, druhá potom analyzuje současný stav. Následuje návrhová část, kde je zahrnuta samotná implementace i finanční zhodnocení pomocí ROSI modelu.

The thesis focuses on the implementation of compliance with the TISAX standard in a company operating in the automotive industry. The first part presents the theoretical basis for the issue, the second part analyses the current state of the art. This is followed by the design part, where the actual implementation as well as the financial evaluation using the ROSI model is included.
Introducing compliance with the TISAX standard into the company
Keywords: TISAX; ISMS; automobilový průmysl; bezpečnost informací; audit.; TISAX; ISMS; automotive industry; information security; audit.